A Preliminary Study of Paleoflood Deposits of the Lukulo, Kebumen Regency, Central Java, based on River Geomorphology - Mareta, Nandian; Lubis, Rachmat F; Ansori, Chusni; Hadian, M Sapari Dwi; P Saputro, Sugeng; Farisan, Ardhan (Faculty of Geography, Universitas Gadjah Mada, 2024)
Lukulo is a river that flows through pre-tertiary rocks to the recent. The long Lukulo fluvial processes which included erosion, transportation, and deposition were depicted in extensive alluvial deposits downstream of the river. This vast alluvial plain may be a deposit result of the Lukulo flood in the past. The paleo-flood study is a study of flood events in the past with the technique used, namely knowing slack water deposits (Steding & Baker, 1987). Delineation of slackwater deposits is necessary to determine the location of paleoflood deposition. Geomorphology of Lukulo watershed is needed as a preliminary study to determine the characteristics of the Lukulo watershed. Based on the analysis of the Lukulo watershed, DEM, with the systematic method of literature review, the result of this watershed geomorphology was obtained, namely; the morphology of the Lukulo watershed included an elongated oblong shape of the watershed, with an average Rc value of all three segments (upstream, middle, and downstream) of 0,52. The average drainage density (Dd) of river flows in the Lukulo watershed is 8,05 km/km2 (middle class). The Lukulo gradient upstream is 450, entering the middle is reduced to 300, and downstream the gradient is reduced to 100. The morphology and morphometry of the Lukulo watershed are interpreted to mean that Lukulo belongs to the medium-spanned watershed in terms of flood runoff and erosion. The lithology is a mixture of impermeable and permeable rocks. Delineation of diluvial and alluvial deposits is found in the upstream, middle, and downstream, of the Lukulo river. It depicts delineated paleoflood deposits in all segments of the river.